Das Rentenpaket 2014 - eine ökonomische Beurteilung - Reinhold Schnabel (Wirtschaftsdienst, 2015)
– The 2014 pension reform has three main components. First disability pensions have been increased by about two earnings points, an average monthly gain of 40 euros. In addition low wages in the four years preceding disability-related retirement will now be disregarded. However, since these new rules only apply to retirement after July 2014 they fail to fight poverty among current disability-related retirees. Second an additional credit for all births before 1992 ('mothers' pension') is extremely costly and unnecessary. Poverty prevention is weak due to a strict income test in the welfare system for the elderly. Third early retirement at age 63 without actuarial adjustment has been reintroduced This is a costly measure with negative effects on both equality and efficiency. The additional child credit and early retirement provisions reduce the financial and social sustainability of the German public pension system.
Keywords: H55; 330; Rentenreform; Wirkungsanalyse; Rentenfinanzierung; Flexible Altersgrenze; Deutschland